2002
DOI: 10.1093/nar/30.1.98
|View full text |Cite
|
Sign up to set email alerts
|

RiceGAAS: an automated annotation system and database for rice genome sequence

Abstract: An extensive effort of the International Rice Genome Sequencing Project (IRGSP) has resulted in rapid accumulation of genome sequence, and >137 Mb has already been made available to the public domain as of August 2001. This requires a high-throughput annotation scheme to extract biologically useful and timely information from the sequence data on a regular basis. A new automated annotation system and database called Rice Genome Automated Annotation System (RiceGAAS) has been developed to execute a reliable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 6 publications
0
84
0
Order By: Relevance
“…Sequence annotation and computational analysis of DNA: The Rice Genome Automated Annotation System (RiceGAAS) (Sakata et al 2002) was used to analyze genomic sequence data. This system integrates the programs GENSCAN, RiceHMM, FGENESH, and MZEF for finding putative gene regions and the homology-search-analysis programs Blast, HMMER, ProfileScan, and MOTIF for predicting the putative functions of genes.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence annotation and computational analysis of DNA: The Rice Genome Automated Annotation System (RiceGAAS) (Sakata et al 2002) was used to analyze genomic sequence data. This system integrates the programs GENSCAN, RiceHMM, FGENESH, and MZEF for finding putative gene regions and the homology-search-analysis programs Blast, HMMER, ProfileScan, and MOTIF for predicting the putative functions of genes.…”
Section: Methodsmentioning
confidence: 99%
“…A total of ‫ف‬ 1000 sequences, which included PCR products filling gaps between the shotgun contigs, were assembled and gave a nucleotide sequence of 71,953 bp. The ‫ف‬ 70-kb sequence was annotated by RiceGAAS (Rice Genome Automated Annotation System [Sakata et al, 2002]; http://ricegaas. dna.affrc.go.jp/index.html), which automatically analyzes large sequences using several programs for the prediction and analysis of protein-coding sequences: BLAST (Basic Local Alignment Search Tool [Altschul et al, 1990]), AutoPredLTR (Sakata et al, 2002), and GENSCAN (Burge and Karlin, 1997).…”
Section: Haplotype-specific Regionmentioning
confidence: 99%
“…NP79R sequence has been shown to be conserved in different S haplotypes of almond (Ushijima et al, 2001 (A) Scheme of the S c haplotype-specific region. The nucleotide sequence of the ‫-07ف‬kb S c haplotype-specific region was characterized by GEN-SCAN, BLASTX, and AutoPredLTR search of RiceGAAS (Sakata et al, 2002). The A nucleotide of the putative initiation codon (ATG) of the S c -RNase gene (Ushijima et al, 1998) is positioned as ϩ1.…”
Section: Cdna Cloning Of the Pollen-expressed Genes Located At The S mentioning
confidence: 99%
“…Two hypothetical genes ( TmHG-1 and TmHG-2 ) were predicted by the RiceGAAS annotation system (Sakata et al, 2002), and corresponding ESTs were found (see supplemental data online). Close to the right end of the contig and upstream of TmSTF-1 , two pseudogenes were found: TmRGL-1 belongs to the NBS-LRR resistance gene analog type, and TmPIK-1 shows similarity to a phosphatidylinositol-3 kinase gene from soybean.…”
Section: Genes and Pseudogenes On The T Monococcum And T Durum Contigsmentioning
confidence: 99%
“…Direct and inverted repeat sequences were identified with the GCG program BESTFIT and dot-plot analysis of the query sequence against itself. For gene prediction in regions in which no putative genes or repetitive elements were identified by BLASTX or BLASTN, the RiceGAAS annotation system (Sakata et al, 2002) was used. Predicted genes were considered if they were predicted by at least two prediction programs.…”
Section: Sequence Analysismentioning
confidence: 99%